Problemática de registro de algunas variables fisiológicas durante el embarazo - Eisenberg, Paulina; Domínguez, Carmen G.; Lindig, Miguel (Revista Mexicana de Ingenieria Biomedica, 2018)
The purpose of this paper is to describe and analyze a method used to evaluate the state of health of mother and phoetus at rest and during exrcise. The method described is non-invasive in nature and is intented to reduce patient discomfort to a minimum. It is considered that the physical exercise undertaken by the patient produces a stress level similar to that produces by normal day to day activity. The results obtained from clinical trials suggest that this method is apropriate for monitoring phoetal activity. The difficulties experienced while recording the phisiological data, as well as the unusual equipment requirements are also discussed and analyzed.